Computed Tomography Simulation for Gamma Knife Radiosurgery: Impact on Target Coverage - Sridhar Yaddanapudi; Steven M. Herchko; Deepak K. Shrestha; Bonita L. Gianforti; Kathleen A. Kopacka; Kayla M. Lane; Anna C. Harrell; W. Christopher Fox; Sanjeet S. Grewal; Daniel M. Trifiletti; Jennifer L. Peterson (Journal of Medical Physics)
This study evaluated the effectiveness of using a traditional computed tomography (CT) simulation scan in the Leksell Gamma Knife® Icon™ workflow for stereotactic radiosurgery. We compared two workflows, one involving a traditional CT simulation co-registered with the magnetic resonance imaging (MRI) and cone-beam CT (CBCT) (MRI-CT-CBCT) and another without the CT scan, co-registering the MRI directly with CBCT (MRI-CBCT). The cohort included 50 frame-based (54 targets) and 55 frameless (124 targets) patients treated between August 2020 and December 2022. Target coverage was assessed by the percentage of each target covered by the prescription isodose line. The mean coverage differences for the frame-based and frameless cohorts were −1.20% ± 1.43% and −1.06% ± 1.51%, respectively, with 95% confidence intervals of −1.59, −0.81 and −1.32, −0.79. The MRI-CBCT workflow was deemed noninferior to the MRI-CT-CBCT workflow. Our data indicate that both workflows yield similar results, suggesting that a traditional CT simulation scan is unnecessary.